PERLINDUNGAN KONSUMEN TERHADAP KEAMANAN DATA PRIBADI DI SEKTOR PERDAGANGAN ONLINE (STUDI TERHADAP KEBOCORAN DATA KONSUMEN SHOPEE): Consumer Protection Against Personal Data Security in the Online Trade Sector (Study of Shopee Consumer Data Leak) - Rafli Syah Maulana; Anna Maria Tri Anggraini (AMICUS CURIAE, 2025)
Personal data theft is a form of cybercrime that is rampant in Indonesia, especially with the main target of the e-commerce sector. The identification of this research problem, namely: how is the legal protection of Shopee consumers' personal data based on Law No. 8 of 1999 concerning Consumer Protection (UUPK) and how is the responsibility of business actors in the event of a Shopee consumer data leak according to the provisions of the UUPK. This research uses normative juridical methods, descriptive in nature, data collected through literature studies and interviews, analysed qualitatively, and deductive conclusions. The results showed that the GCPL guarantees consumers' rights to obtain comfort, security, and safety in utilising the services offered by business actors. This is reinforced by Minister of Communication and Informatics Regulation No. 20/2016 on the Protection of Personal Data in Electronic Systems which gives consumers the right to file reports and demands to the competent authority in the event of a violation of personal data. The author recommends that the Ministry of Communication and Digital (Komdigi) take concrete steps in the form of temporary suspension of transaction activities on platforms proven to violate personal data protection.